Modelling torque and temperature in friction stir welding of aluminium alloys. (15th September 2020) - Andrade, D.G.; Leitão, C.; Dialami, N.; Chiumenti, M.; Rodrigues, D.M.
Highlights: Tool dimensions and the tool rotational are the main factors governing heat generation and torque evolution. The tool traverse speed and the plate thickness have a strong influence on heat dissipation and on torque, but mainly in thick plates welding. Torque and temperature evolution with process parameters is similar for the different aluminium alloys series. Analytical coefficients were determined for calculating the welding temperature ( CT ) and the torque ( CM ) under different welding conditions. A threshold in heat generation was determined for CT > 20, 000. Abstract: An analysis of the evolution of the torque and of the temperature with welding conditions, in Friction Stir Welding (FSW) of aluminium alloys, was conducted. More precisely, torque and temperature results from a large number of publications, on FSW of AA2xxx, AA5xxx, AA6xxx and AA7xxx aluminium alloys series, were collected. The literature data was complemented with results from a fully coupled thermomechanical analysis of the FSW welding process. Coupling the experimental data, from the literature, with numerical simulation results, the individual influence of the main process parameters, tools and plates characteristics, on the torque and on the temperatures in FSW was assessed. It was found that the tool rotational speed govern the heat generation, while the tool dimensions have a very important influence, not only on the heat generation but also on the volume of material being stirred during welding, which is another important factor determining the welding torque. The traverse speed and the base material thickness were also found to be important factors governing the torque during welding. However, the influence of the traverse speed on torque evolution is conditioned by the tool dimensions. A parametric analysis enabling to understand the relation between process parameters, heat generation, heat dissipation and base material stirring, was conducted. Analytical relations, which enable calculating the torque and the temperature, in FSW of aluminium alloys, were developed based on numerical results and tested using the data from the literature review. Graphical abstract: Image, graphical abstract